Investigating the Effectiveness of Edmodo on EFL Learners’ Motivation in Writing Class - Bayu Andika Prasatyo; Devian Try Gustary (Journal of English Teaching, 2023)
This study aims at scrutinizing the effectiveness of the utilization web-based learning platform, Edmodo in teaching academic writing to EFL learners. This study employed a mixed method approach on the fifth-semester students and confirmed that 10 students take part in this study. A mixed method approach was utilized in this study which applied questionnaires to gain quantitative data. Meanwhile, the qualitative data were attained through semi-structured interviews to measure the effectiveness of the Edmodo application in writing class. The findings revealed that 88% of students prefer to learn writing skills using the Edmodo learning platform through collaborative tasks. The research findings illustrated that there was an improvement and students’ interest in writing by applying the Edmodo learning platform. Besides, students find Edmodo as a user-friendly media, and easy to use. Edmodo has helped and developed their writing creativity and their cognitive skills and social interaction with peers are also positively developed. This confirmed that there were enough shreds of evidence of how Edmodo was said to be effective in fostering EFL learners' motivation in writing.